Palihan hikayat sa panitikan at malikhaing pagsulat - Evasco, Eugene Y.; Ortiz, Will P.; Antonio, Lilia F. (Quezon City C & E Pub., 2008)
On study and teaching of Philippine literature and creative writing.
In Tagalog.
Keywords: Philippine literature -- Study and teaching (Higher); Creative writing (Higher Education) -- Philippines; Philippine poetry; Short stories, Philippine